Reform of income splitting for married couples: Only individual taxation significantly increases working incentives - Stefan Bach; Johannes Geyer; Peter Haan; Katharina Wrohlich (DIW Economic Bulletin, 2011)
The joint taxation of married couples in Germany with full income splitting is still a major hindrance to the participation of married women in the labor market. In their current financial proposals, the SPD (Social Democratic Party) is calling for income splitting for married couples to be replaced by individual taxation with maintenance deductions, in accordance with existing schemes for divorced spouses. Simulations implemented by DIW Berlin show that such a reform would only have limited effects on distribution and labor supply. Pure individual taxation, however, would not only lead to significant additional tax revenue but would also considerably increase the number of married women participating in the labor market. If politicians take the goal of greater integration of married women in the labor market seriously, then the current income splitting for married couples would have to be replaced by individuation taxation.
Keywords: H24; H31; J22; 330; working incentives; joint taxation of couples; female labor supply